2016
DOI: 10.21037/tlcr.2016.06.13
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lymph node ratio in patients with pathological N1 non-small cell lung cancer: a systematic review with meta-analysis

Abstract: Background: Non-small cell lung cancer (NSCLC) patients with N1 disease have variable outcomes, and additional prognostic factors are needed. The number of positive lymph nodes (LNs) has been proposed as a prognostic indicator. However, the number of positive LNs depends on the number of LNs examined from the resection specimen. The lymph node ratio (LNR) can circumvent this limitation. The purpose of this study is to evaluate LNR as a predictor of survival and recurrence in patients with pathologic N1 NSCLC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The results of a number of clinical retrospective studies from all over the world, including studies on different ethnic groups, are consistent with our results based on the SEER database. A meta-analysis of five retrospective studies representing 6,130 non-advanced NSCLC patients from the United States and China indicated that the pLNR could be used to predict the OS and disease-free survival (DFS) of patients and detected no publication bias (22). According to clinical research, the pLNR can be used to assess not only the prognosis of early-stage NSCLC patients but also the risk of brain metastasis in late-stage NSCLC patients (23).…”
Section: Discussionmentioning
confidence: 99%
“…The results of a number of clinical retrospective studies from all over the world, including studies on different ethnic groups, are consistent with our results based on the SEER database. A meta-analysis of five retrospective studies representing 6,130 non-advanced NSCLC patients from the United States and China indicated that the pLNR could be used to predict the OS and disease-free survival (DFS) of patients and detected no publication bias (22). According to clinical research, the pLNR can be used to assess not only the prognosis of early-stage NSCLC patients but also the risk of brain metastasis in late-stage NSCLC patients (23).…”
Section: Discussionmentioning
confidence: 99%
“…This latter practice improves the accuracy of staging and prognostication, 65 and there is also evidence that this practice reduces mortality. [66][67][68] M classification remains a relatively rare occurrence in the handling of resection specimens. Pathologists should not conclude the reports as pM0, but rather leave this as blank unless there is evidence of metastatic disease, in which case pM1a and pM1b or pM1c should be assigned.…”
Section: Lung Cancermentioning
confidence: 99%
“…Ratio of the Metastatic Lymph nodes (RML) is the ratio between metastatic and examined lymph nodes which sometimes is termed as Lymph Node Ratio (LNR). It is suggested RML (or LNR) provided independent prognostic data in NSCLC in all N stages [ 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%